Answer:
-1
Step-by-step explanation:
using PEDMAS(parentheses, exponents, division, multiply, addition, subtraction) to solve the problem
First, multiply (-5)(2) and 2(-3)
(-5)(2) – 2(-3) + 3
=-10-(-6)+3
=-10+6+3
add -10+6
-4+3
Add -4+3
-4+3
=-1
Therefore, (-5)(2) – 2(-3) + 3 is equal to -1
Answer: yes
Step-by-step explanation:
Answer:
8
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Step-by-step explanation:
<u>Step 1: Define</u>
6(x - 2) = 36
<u>Step 2: Solve for </u><em><u>x</u></em>
- Divide 6 on both sides: x - 2 = 6
- Add 2 on both sides: x = 8
Answer:
1. 35
2. 145
3. 55
4. 90
5. 145
Step-by-step explanation:
1. 35: angle 1 and 2 are a linear pair (meaning it is in one line and adds to 180). Since we know angle 2 is 145, ∠1 = 180 - 145
∠1 = 35
2. 145: ∠7 = ∠2 because they are alternate angles and alternate angles are equal
3. 55: ∠7 = ∠5 + ∠4 because vertically opposite angles are equal. We know that ∠5 = 90, hence ∠4 would equal 145 - 90 = 55
4. ∠5 = 90. It is given
5. 145: ∠9 = ∠2 because they are vertically opposite